RESEARCH REGARDING THE INFLUENCE OF BETA IRRADIATION ON THE ENZYMATIC ACTIVITY OF BAKER’S YEAST - ENIKŐ GAŞPAR (Scientific Papers Animal Science and Biotechnologies, 2023)
The biotechnological properties and the maltase activity of baker’s yeast were investigated by irradiation with beta radiations in doses of 9.76 Gy, 12.20 Gy, 17.08 Gy and 22.96 Gy. We observed that the maltase activity is greater in yeast irradiated with lower doses (9.76 Gy, 12.20 Gy and 17.08 Gy) indicating that the beta radiation have a stimulating effect on the fermenting capacity of baker’s yeast. This fact is valid also after 90 days. A higher dose induces a regress of this process. The baker’s yeast exposed at beta radiations produced cultures more vigorous, resistant and with higher biotechnological properties.